Parameters of blood viscoelasticity testing as promising biomarkers for the prediction of the occurrence of diabetic peripheral neuropathy - Yong Zhuang; Xin Hu; Qingyan Cai; Huibin Huang (BMC Endocrine Disorders)
Abstract Aims Research suggested that fibrinogen is associated with diabetic peripheral neuropathy (DPN). Our previous study unveiled that fibrinogen function indices, namely the k value and angle α, have the potential to serve as early diagnostic indicators for DPN. However, it has yet to be reported whether these factors influence the development of DPN. Here, type 2 diabetes were followed up for two years to investigate whether k value and angle α impact the onset of DPN. Methods Type 2 diabetes without neuropathy were recruited for this prospective observational clinical study and were followed up for two years. Participants were categorized into three groups based on progression to DPN: diabetes without neuropathy, subclinical DPN, and confirmed DPN. Differences in baseline parameters were compared, and independent risk factors were analysed. Results Participants who progressed to DPN (both subclinical DPN and confirmed DPN) had higher baseline levels of HbA1c than in those who did not (P = 0.015; P = 0.040). The baseline angle α was also greater (P < 0.001; P < 0.001), while the k value was lower in participants who progressed to DPN than in those who did not (P < 0.001; P < 0.001). The associations of the angle α and k value with DPN were independent of HbA1c, duration, fibrinogen (Fib) and other potential confounders affecting the angle α and k value (e.g., vitamin B12, retinopathy, and renal status). ROC curve indicated that the predictive value of the angle α and k value were 0.759 and 0.804. Conclusions Fibrinogen function indices could potentially be utilized as predictive indicators for evaluating the likelihood of DPN in diabetes.